Justiça na teoria dos sistemas autopoiéticos - Viana Filho, Flávio (2013)
This research aims at the analysis of environmental justice within the sociological systems theory of niklas luhmann. To this end, considerations are developed on the decision on the legitimacy of law and justice on the conceptualization of that author. The final chapter is devoted to analysis of recent case examined by the stj and that, by nature, you can configure the practical application of "contingency formula" of the legal system.